Hydrogen Bond‐Functionalized Massive Solvation Modules Stabilizing Bilateral Interfaces. (10th February 2022) - Chen, Wenyong; Guo, Shan; Qin, Liping; Li, Lanyan; Cao, Xinxin; Zhou, Jiang; Luo, Zhigao; Fang, Guozhao; Liang, Shuquan
Abstract: Although mild aqueous electrolytes endow zinc‐ion batteries with intrinsic security surpassing that of lithium‐ion batteries, whether irreversible zinc deposition and related corrosion on the anode or cathode species dissolution severely circumscribes their cyclic stability, especially at low current density. Here, hydrogen bond‐functionalized massive solvation modules in a maltose‐based hybrid electrolyte are constructed, which is crucial for the stability of bilateral interfaces in the cycling process, to address this infamous issue. The intensive solvated interactions and diffusion hindrance effect yield uniform deposition of zinc at the anode interface, while the hydrogen bond confinement to free water interdicts derived parasitic reactions. As for the cathode interface, the massive solvation modules avoid structural framework collapse from vanadium dissolution and preserve low interfacial activation energy during cycling. The above bilateral interface regulation enables resultant full batteries to unprecedentedly maintain 84.2% of its initial specific capacity after 400 continuous cycles even at a very low current density of 50 mA g –1 . This work provides a new perspective toward economical and eco‐friendly electrolytes for stable aqueous batteries. Abstract : The hydrogen bond‐functionalized massive solvation modules in the electrolyte conduct uniform zinc electrodeposition at the anode interface arising from the concomitant 3D–2D associative hindrance effect, while the hydrogen bond confinement to free water interdicts derived parasitic reactions. Synchronously, the massive solvation modules avoid structural framework collapse from vanadium dissolution and preserve low interfacial activation energy during cycling.